Anticancer Screening of Ru(II) Photoredox Catalysts at Single Cancer Cell Level. Issue 9 (21st March 2023) - Fan, Zhongxian; Xie, Jiaen; Kushwaha, Rajesh; Liang, Shaoxia; Li, Wenqing; Mandal, Arif Ali; Wei, Li; Banerjee, Samya; Huang, Huaiyi
Abstract: The rapid efflux of Pt‐based chemotherapeutics by cancer cells is one of the major causes of drug resistance in clinically available drugs. Therefore, both the high cellular uptake as well as adequate retention efficiency of an anticancer agent are important factors to overcome drug resistance. Unfortunately, rapid and efficient quantification of metallic drug concentration in individual cancer cells still remains a tricky problem. Herein, with the help of newly developed single cell inductively coupled plasma mass spectrometry (SC‐ICP‐MS), we have found that the well‐known Ru(II)‐based complex, Ru3, displayed remarkable intracellular uptake and retention efficiency in every single cancer cell with high photocatalytic therapeutic activity to overcome cisplatin resistance. Moreover, Ru3 has shown sensational photocatalytic anticancer properties with excellent in‐vitro and in‐vivo biocompatibility under light exposure. Abstract : We report a biocompatible and lysosome‐targeting Ru(II)‐based photoredox catalyst to overcome the cisplatin‐resistance on green light exposure at the single cell level.